Pengaruh Suku Bunga Acuan dan Financing To Deposit Ratio (FDR) terhadap Tingkat Distribusi bagi Hasil Deposito Mudharabah pada PT. Bank Sumut Syariah - Zaini Ahmad; Tuti Anggraini; M. Ikhsan Harahap (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
Bank Sumut Syariah in Indonesia is a bank that carries out its business in accordance with Islamic principles. This research aims to determine the effect of reference interest rates and Financing to deposit ratio (FDR) on the distribution level of profit sharing from mudharabah deposits at PT. North Sumatra Sharia Bank. This research uses a quantitative approach, with the data source used is secondary data. This research uses secondary data and literature study from 2018-2022. Secondary data is a source of research data obtained by research indirectly through intermediary media (obtained and recorded by other parties). The analysis techniques used in this research include classical assumption test analysis, linear regression test, hypothesis test, namely the t test, F test and coefficient of determination (R2) using SPSS 20 software. The research results show that it partially explains the value of the interest rate. Reference and Financing to Deposit Ratio (FDR) have a significant and positive effect on the distribution level of profit sharing from mudharabah deposits. Then partially explained that simultaneously the Reference Interest Rate (X1), Financing to Deposit Ratio (FDR) (X2), had a significant and positive effect on the level of distribution of profits from mudharabah deposits at PT. North Sumatra Sharia Bank.